Abnormal communication between cephalic and basilic veins-a case report - Nayak, Gyanaranjan; Sahoo, Niranjan; Pradhan, Sujita (International Journal of Research in Medical Sciences, 2023)
The cephalic vein and basilic vein begin respectively from lateral and medial ends of the dorsal venous arch of hand. The basilic vein is confined to the medial side of upper limb and continues upwards as the axillary vein whereas the cephalic vein is confined to the lateral side of upper limb and drains into the axillary vein. The aforesaid veins communicate with one another through the median cubital vein that lies in the roof of cubital fossa. The superficial veins are used for venepuncture, cardiac catheterization, bypass grafting and arteriovenous fistula for hemodynamic access. The authors chanced upon a variation in the cephalic and basilic veins in the right upper limb of a cadaver of a sixty years old female dying due to natural causes. The cadaver was used for routine dissection classes of first year MBBS students in a medical college of Eastern India. The cephalic and basilic veins of the said cadaver joined with each other in the cubital fossa. The brachial vein began from the point of union of the two former superficial veins and the single brachial vein replaced the paired brachial veins which is usually the norm.